2011
DOI: 10.1017/s0022029911000562
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of serum protein fractions in dairy cows during different stages of gestation and lactation

Abstract: In dairy cows the period of transition from late gestation to early lactation is recognized as inducing considerable metabolic adaptation. The aim of this study was to analyse modifications in serum protein values occurring during the dry and the transition period and during lactation in a group of five Holstein cows of high average milk production. For all subjects, selected on the basis of their pregnancy status, blood samples were collected at different physiological phases: dry period (-60, -30 d to calvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 21 publications
10
36
2
1
Order By: Relevance
“…The results of our study indicate that levels of α1-globulins, α2-globulins, β-globulins and γ-globulins were statistically significant increase in camels suffering from parasitic infection comprised to healthy. The results were in agreement with many studies (Alberghina et al, 2010, Piccione et al, 2011Tóthová et al, 2013). Serum protein electrophoresis standard method for fractionation and quantification of serum proteins is electrophoresis in clinical biochemistry.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 93%
“…The results of our study indicate that levels of α1-globulins, α2-globulins, β-globulins and γ-globulins were statistically significant increase in camels suffering from parasitic infection comprised to healthy. The results were in agreement with many studies (Alberghina et al, 2010, Piccione et al, 2011Tóthová et al, 2013). Serum protein electrophoresis standard method for fractionation and quantification of serum proteins is electrophoresis in clinical biochemistry.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 93%
“…Serum protein profile did not reveal differences between fetus' sire or by CBW class; this implies that g-globulin were unaffected, and therefore the immune system for the passive transfer of immunity was not compromised with CLONE progeny or with increased CBW. The absolute values of a 1 -globulin in this article are slightly lesser than those reported by Piccione et al [30]; this fraction is generally associated to a group of acute-phase proteins that are signal of inflammatory conditions [31]. In the light of our results, also bglobulin did not differ between the 2 groups of recipients.…”
Section: Discussioncontrasting
confidence: 67%
“…Grunberg et al (2011) observed lower concentrations of total serum proteins in cows around parturition than outside the parturient period and in the following phases of lactation, which may be associated with the transfer of immunoglobulins from the bloodstream to the mammary gland for the synthesis of colostrum (Roubies et al 2006). Piccione et al (2011;Piccione et al 2012b) found increasing values of α-globulins in dairy cows and ewes post-partum, which may be related to the higher concentrations of the acute phase proteins in response to the processes occurring around the time of parturition.…”
Section: Serum Protein Pattern Variations Related To Non-pathologicalmentioning
confidence: 99%